2016
DOI: 10.1007/s00402-016-2445-5
|View full text |Cite
|
Sign up to set email alerts
|

Are people following hip and knee arthroplasty at greater risk of experiencing a fall and fracture? Data from the Osteoarthritis Initiative

Abstract: There appears a lower chance of experiencing a fracture for people following THA compared to those who have not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 31 publications
(29 reference statements)
1
16
2
Order By: Relevance
“…Several investigators have identified hip abductor muscle strength as a contributing factor to stability during standing and walking. 27,28 Ikeda et al 18 Previous studies reported the prevalence of falls during the first year after THA was 25% to 32% 10,11,29 , which was similar to the results of the present study. Additionally, our findings that falls commonly occurred indoors, during the daytime, and resulted from tripping are consistent with the findings of Ikutomo et al 10 who examined the incidence of falls in patients after THA (50.0% indoors, 66.2% during the daytime, 47.1% because of tripping, and 5.9% had fractures).…”
Section: Discussionsupporting
confidence: 91%
“…Several investigators have identified hip abductor muscle strength as a contributing factor to stability during standing and walking. 27,28 Ikeda et al 18 Previous studies reported the prevalence of falls during the first year after THA was 25% to 32% 10,11,29 , which was similar to the results of the present study. Additionally, our findings that falls commonly occurred indoors, during the daytime, and resulted from tripping are consistent with the findings of Ikutomo et al 10 who examined the incidence of falls in patients after THA (50.0% indoors, 66.2% during the daytime, 47.1% because of tripping, and 5.9% had fractures).…”
Section: Discussionsupporting
confidence: 91%
“…Two studies used the same cohort; however, had different primary objectives [30, 32]. Six studies were cross-sectional studies [2530] of which one was an abstract [27], four were prospective cohort studies [18, 3133], and two were retrospective cohort studies [34, 35] (Additional file 2: Table S1). Eight studies [2529, 32, 33, 35] had a comparison group, comparing self-reported “fallers” to “non-fallers”.…”
Section: Resultsmentioning
confidence: 99%
“…Six studies used a traditionally accepted definition of falls [25, 26, 3033], which was “an unexpected event in which the participant comes to rest on the ground, floor, or lower level, not as a result of a major intrinsic event such as a faint or stroke, seizure, or an overwhelming external hazard”. The remaining studies did not explicitly define what constituted a fall in their study population [18, 2729, 34, 35]. Sample sizes ranged from 31 to 413 participants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other knee OA–related outcomes, such as knee arthroplasty and knee instability, have been examined in regard to falls. Interestingly, adults with knee arthroplasty do not appear to have an increased risk of falls compared with adults without knee arthroplasty , whereas knee instability has been shown to be associated with a greater prevalence of recurrent falls . Yet, injurious falls are an outcome of greater clinical and public health relevance .…”
Section: Introductionmentioning
confidence: 99%